Evaluasi Implementasi Sistem Manajemen Keselamatan Konstruksi (SMKK) pada Pembangunan Gedung Kuliah FT (B, C, dan D) Universitas XYZ - Zika Dwi Zahara; Ari Syaiful Rahman Arifin (Lembaga Yasin AlSys, 2026)
The implementation of the Construction Safety Management System (SMKK) in construction projects is an important aspect for ensuring worker safety, environmental protection, and work continuity. This study aimed to analyze the level of SMKK implementation, evaluate its compliance with Minister of Public Works and Housing Regulation No. 10 of 2021, and identify supporting and inhibiting factors in its implementation in the construction project of the Faculty of Engineering Lecture Buildings (B, C, and D) at XYZ University. This study used a mixed-methods approach with an evaluative descriptive design, involving 22 respondents selected through purposive sampling and total sampling techniques. Data were collected through questionnaires, interviews, observation, and documentation, and were then analyzed using descriptive statistics, data triangulation, member checking, and gap analysis. The results showed that the level of SMKK implementation was in the appropriate category, with an average score of 89.68%. The compliance evaluation showed that all main elements of SMKK had met regulatory provisions and did not show any significant gap with actual conditions in the field. Supporting factors in SMKK implementation included leadership commitment, availability of resources, workforce competence, and structured safety documentation, whereas inhibiting factors included consistency in procedure implementation and discipline in the use of personal protective equipment. The conclusion of this study confirms that the implementation of SMKK in construction projects requires continuous supervision, safety training, and strengthening of safety culture to support the sustainability of an occupational safety system that complies with regulatory provisions.